HUBUNGAN ANTARA INTENSITAS MENONTON SINETRON PERCINTAAN REMAJA DENGAN GAYA HIDUP HEDONIS SISWA SMA YOS SUDARSO CILACAP - Eryanti, Mega Yuni (Universitas Ahmad Dahlan, 2014)
ABSTRACTÂ This study aimed to determine the relationship between intensity of watching a romantic drama with teenagerâs hedonism lifestyle. The subject of this study was high school students of XI grade at Cilacap Yos Sudarso. The research method of the study used quantitave approach by using a questionnaire. The intensity of watching a romantic Drama Scale and Hedonism Lifesty scale was used to collect the data. Cluster random sampling was used to get the sample of this study. The results of data analysis showed that the correlation between variables was significant (rxy = 0.449; p <0.01). Means that there is a significant positive relationship between the intensity of watching a romance drama with hedonism lifestyle. The higher the intensity of watching a romantic drama, the higher the hedonism lifestyle of student. Conversely the lower the intensity of watching a romantic drama, the lower lifestyle of hedonism among student. The effective contribution of watching soap operas on hedonistic lifestyle was 20.2%. The categorization of data showed that most subjects (51.06%) had a higher intensity of watching romantic drama and 50% of student had higher hedonism lifestyle category.Â Keywords: intensity watching romantic drama, and hedonism lifestyle.Â